Cardiac macrophages prevent sudden death during heart stress - Junichi Sugita (Nature Portfolio, 2021)
Cardiac immune cells play various roles in the maintenance of homeostasis and diseases in the heart. Here the authors show that cardiac resident macrophages are a critical regulator of cardiac impulse conduction through amphiregulin production, contributing to the prevention of sudden death.